Sociodemographic and clinical features of patients with alcohol and substance use disorders in a specialized unit - Asan, Ömer; Tıkır, Baise; Okay, İhsan Tuncer; Göka, Erol (Journal of Dependence, 2015)
Objective: The aim of the study was to investigate the socio-demographic characteristics of substance abusers and characteristics of substance use of patients who were applied to the Alcohol-Substance usage disorders unit of Ankara Numune Education and Research Hospital.Method: In this study the alcohol and substance users, who have applied Alcohol-Substance usage disorders unit of Ankara Numune Education and Research Hospital between 1-15 January 2013, have been interviewed. Also a semi-structured questionnaire has been used.Results: Of 302 patients, 283 were men and 19 were women. According to the choice of drugs, 14.6% was alcohol users, 53.3% was heroin users, 5.6% was cannabis users, 3.6% was other drug users (cocaine, ecstasy, volatile) and 22.8% was mixt drug users. This study revealed that there was a great deal of drug and alcohol users in the family of the drug alcohol users (30,5%). The study showed that 21.5% of the patients were having legal problems before they start using alcohol-substance and 36.4% of the patients having legal problems after they start using alcohol-substance. It was found that 24.4% of the heroin users were IV users. The 55.8% of IV users have used the needle of other IV drug users. It has also been observed that 9.5% of them never sterilized the needle they used. The 58.9% of patients have not read any book and 31.8% have not read newspaper. The study showed that the cannabis users were making some activities like reading book-newspaper, going to cafe with friends, travelling to other cities more often than the other groups of users. Also the study showed that 19.9% of the patients have not sustained education, 47% have lost job and 22.5% had an accident because of alcohol-drug using.Conclusion: It was noticeable that there was a great deal of drug and alcohol users in the family of patients. It has been noticed that the social status of cannabis users were better being protected when compared to the other groups of users. As a result of the use of alcohol and substance, they were losing their jobs and this situation showed that the families of alcohol and substance users were being victims. The results of this study show that; the alcohol and substance abuse negatively affects many areas of life like social life, family and community relationships, job and education. Also alcohol and substance abuse causes increased illegal activities and disrupts the public peace. The alcohol and substance abuse is being a greater problem day to day, so for treatment a multidisciplinary approach should be developed which contains editing the social life, family and community relationships, the education and work life along with pharmacological treatment.
Keywords: Socio-demographic characteristics; substance dependence; crime